Polyp as unusual cause of gastric subocclusion. Case Repor - Marcos Félix Osorio Pagola; Mayelin González Pérez; Jesús Iván González Batista; Omar Julián Hernández Ojeda; Anagalys Ortega Alvelay (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
This paper presents a case report of a 27 years old female that entered in the Gustavo Aldereguía Lima Hospital of Cienfuegos with diagnosis of Pyloric Syndrome. Endoscopic examination showed a gastric polyp with pedicle located at level of the pylorus that occluded parcially it and passing through it toward the duodenal bulb. Endoscopic excision was carried out without complications being solved the clinical situation.